Functionalized Amide Chlorides: 5-Dimethylamino-1H-Tetrazoles from N,N-Dimethyl-Azidochloromethylenimonium Chloride and Primary amines - H.G. Viehe; P. George (CHIMIA)
Sodium azide or trimethylsilylazide react with N,N-dimethylphosgenimonium chloride by monosubstitution yielding N,N-dimethyl-azidochloromethylen-imonium chloride which can be isolated. This compound is characterized both spectroscopically and by facile reactions with primary amines affording 1-substituted-5-dimethyl-amino-tetrazoles.